MODEL DISCOVERY LEARNING SEBAGAI STRATEGI PEMBELAJARAN FISIKA UNTUK MENINGKATKAN KEMAMPUAN PSIKOMOTORIK PESERTA DIDIK - Nurihwana, Riza; Kuniawan, Eko Setyadi; Ashari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to understand the implementation of the Discovery Learning model on students' psychomotor skills and the improvement of these skills during the application of the Discovery Learning model in the subject of Vibration and Waves at SMPN 15 Purworejo. This research is a classroom action research (CAR) aimed at addressing problems found in the classroom. The subjects of the study were 32 students from class VIII B in the 2023/2024 academic year. The research was conducted in two cycles. Data collection techniques included observation sheets, learning outcome tests, questionnaires, and documentation. The results of the study show that the implementation of the Discovery Learning model in teaching Vibration and Waves can enhance students' psychomotor skills. This is evident from the increase in students' psychomotor skills from 75% in Cycle I to 88% in Cycle II. Students' knowledge learning outcomes are also reflected in the class average scores, which improved from 75.94 in Cycle I to 88.12 in Cycle II. Thus, there is an improvement in students' psychomotor skills through the implementation of the Discovery Learning model at SMP Negeri 15 Purworejo.